Beet-sugar handbook - Asadi, Mosen (Wiley-Interscience, 2007)
This book is a practical and concise reference for technologists, chemists, farmers, and research personnel involved with the beet-sugar industry. It covers: Basics of beet-sugar technology, Sugarbeet farming, Sugarbeet processing, Laboratory methods of analysis, The book also includes technologies that improve the operation and profitability of the beet-sugar factories